Technological complex for production, transportation and storage of gas from the offshore gas and gas hydrates fields - Pedchenko, М.; Pedchenko, L. (Розробка родовищ, 2016)
Purpose. Substantiation and development of schematics acceptable for the existing technological methods of natural gas production and transportation from the offshore fields of gas or gas hydrates. Improvement of their efficiency by way of maximum reduction of energy consumption as the result of complex consideration of thermal and physical properties and parameters of the system components interaction in the deposit under development. Methods. Analysis and generalization of the results of complex experimental research performed on the multifunctional laboratory gas hydrate installation. Findings. The technology of gas hydrates extraction from the productive reservoir without energy consumption for the phase transition is proposed. It is proved that simultaneous development of gas hydrate fields and gas fields via binding free gas into gas hydrate by ensuring necessary temperature and pressure conditions during gas passing through the sea waterbody is expedient. The feasibility of combining in one chain the proposed technology of the developing the offshore gas and gas hydrate fields with technology of gas transportation in hydrate form and its preservation in ground storages is proved. Originality. It was substantiated that gas hydrates can be extracted from the productive reservoir without energy consumption for dissociation, by creating conditions of its recrystallization as a result of joint actions of submerged jets of sea water in the mixture with abrasive material and pressure fluctuations. Practical implications. The proposed gas hydrate technology creates important prerequisites for the development of small and medium remote gas deposits (including gas hydrate ones), the network of ground hydrates storages, improves the efficiency and competitiveness of technology for marine transportation of natural gas in hydrate form